A study on dietary recall among the maintenance haemodialysis patients in East Godavari district. - Dr. P Sasanka; Dr. T Jaya Chandra (International Journal of Medical Research and Review, 2021)
Introduction: Individuals with end-stage renal diseases are usually at an increased risk of nutritional disorders. Protein-energy malnutrition is observed in a significant number of maintenance haemodialysis (MHD) patients. Hence a study was conducted to find whether dietary intake meets recommended dietary allowance (RDA) among MHD individuals. Materials and methods: This was cross-sectional research conducted in the department of Nephrology, GSL Medical College, for 18 months. Individuals are aged 18 years or more, metabolically stable and undergoing MHD were included. Software called Dietsoft was used to know the dietary calculations. Parameters including energy, carbohydrates, proteins, fats, vitamins, minerals and essential amino acids (EAA) were evaluated. Mann Whitney U test was used to find the significant difference, and P < 0.05 was considered statistically significant. Results: Of the 31 patients, 18 were male, and 13 were female. The calorie intake was as recommended, but statistically, there was no significant difference. But the intake of the macronutrients and dietary fibre was higher than the recommended, which was statistically significant. In females, there was a considerable difference. The difference was statistically not significant in minerals intake. Conclusion: There was considerable malnutrition among the patients undergoing MHD. Hence regular dietary assessment is required.